Co0·5Ni0·5FeCrO4 spinel nanoparticles decorated with UiO-66-based metal-organic frameworks grafted onto GO and O-SWCNT for gas adsorption and water purification - Ashtiani, S; Khoshnamvand, M; Shaliutina-Kolešová, A; Bouša, D; Sofer, Zdeněk; Friess, K (Chemosphere, 2020)
We report on the synthesis of unique nanocomposites based on graphene oxide (GO) and oxidized single-wall carbon nanotubes (O-SWCNTs) combined with UiO-66-NH2 and UiO-66-COOH metal-organic frameworks (MOFs) decorated onto Co0·5Ni0·5FeCrO4 spinel magnetic nanoparticles (SMNPs). Novel SMNPs of Co0·5Ni0·5FeCrO4, synthesized for the first time by the sol-gel method, exhibited exceptional thermal stability up to 985 °C. To modify the physicochemical properties of the SMNPs and MOFs, hydrophilic Zr-based MOFs were directly decorated onto the SMNP (MOF-d-SMNP) which led to improved dispersion properties and enhanced the catalytic activity of the SMNP by providing additional functional groups and active catalytic sites, along with surface area expansion. The synthesis and decoration were achieved by a hydrothermal process forming covalent bonding of MOFs onto the SMNPs, using O-SWCNTs and GO monolayers as platforms. Such an approach proved to be more effective than direct mixing of nanoparticles with the platforms, as it reduced the aggregation of nanoparticles and improved the dispersion forces of the MOF-d-SMNP. The MOF-d-SMNP/GO and MOF-d-SMNP/O-SWCNT nanocomposite properties were characterized by XRD, SEM-EDS, HRTEM, FTIR, TGA, gravimetric gas sorption and BET techniques. Performed experiments revealed exceptional adsorption capacity and catalytic activity (the reduction of the toxic pollutant 4-nitrophenol to 4-aminophenol). We demonstrated that novel nanocomposite materials MOF-d-SMNP/GO and MOF-d-SMNP/O-SWCNT showed potential for water treatment and gas sorption applications. Exhibited properties make these materials promising candidates for use in applications requiring, for example, catalytic activity at elevated temperatures.
Keywords: Nanocomposites; Aluminum Oxide; Graphite; Water Purification; nanokompozity; Nanoparticles; Nanotubes, Carbon; Oxidation-Reduction; nanočástice; oxid hlinitý; adsorpce; porézní koordinační polymery; Adsorption; Metal-Organic Frameworks; Magnesium Oxide; Catalysis; katalýza; oxidace-redukce; oxid hořečnatý; čištění vody; grafit; nanotrubičky uhlíkové